Smart levee in Poland. Full-scale monitoring experimental study of levees by different methods - Sekuła, Klaudia; Borecka, Aleksandra; Kessler, Daniel; Majerski, Patryk (Wydawnictwa AGH, 2017)
This paper presents two types of control and measurement networks used in the levee built as part of the ISMOP project. The first control and measurement network based on pore pressure and temperature sensors. Additionally, it contains the fiber-optic technology. The second network include design experimental sensors, constructed for the development of solutions that can be used in existing flood embankments.
Computer Science
Bibliogr. s. 382-384.
Keywords: ISMOP; smart levee; pore pressure measurement; temperature measurement